Kinematic and dynamic analysis of three-mass oscillatory system of vibro-impact plate compactor with crank excitation mechanism - Korendiy, Vitaliy; Kachur, Oleksandr; Gursky, Volodymyr; Gurey, Volodymyr; Maherus, Nadiia; Kotsiumbas, Oleh; Havrylchenko, Oleksandr (Vibroengineering Procedia, 2022)
The paper is aimed at studying the motion conditions of the vibratory compacting machine equipped with the crank excitation mechanism characterized by the changeable geometrical parameters. Unlike numerous scientific publications devoted to similar subject, the novelty of the present research consists in the improved design of the vibro-impact plate compactor and the developed mathematical model describing the motion conditions of the compactor’s oscillatory system. It is proposed to use the crank mechanism to excite the oscillations of the impact body acting upon the frame of the compacting plate at a certain angle to the surface being compacted. The main idea of this improvement is to provide the self-propelling locomotion conditions of the compactor and to reduce the pushing force that must be applied by the operator. The research results obtained by means of the numerical modeling in Mathematica software describe the dynamic behavior of the compactor’s oscillatory system under different geometrical parameters of the crank excitation mechanism (crank eccentricity, impact gap, etc.). The material of the paper can be of significant practical interest for the designers and engineers dealing with the development of new vibratory compactors and the improvement of compacting technologies.